Intraseasonal Drainage Network Dynamics in a Headwater Catchment of the Italian Alps. Issue 4 (6th April 2020) - Durighetto, N.; Vingiani, F.; Bertassello, L. E.; Camporese, M.; Botter, G.
Abstract: In the majority of existing studies, streams are conceived as static objects that occupy predefined regions of the landscape. However, empirical observations suggest that stream networks are systematically and ubiquitously featured by significant expansion/retraction dynamics produced by hydrologic and climatic variability. This contribution presents novel empirical data about the active drainage network dynamics of a 5 km 2 headwater catchment in the Italian Alps. The stream network has been extensively monitored with a biweekly temporal resolution during a field campaign conducted from July to November 2018. Our results reveal that, in spite of the wet climate typical of the study area, more than 70% of the observed river network is temporary, with a significant presence of disconnected reaches during wet periods. Available observations have been used to develop a set of simple statistical models that were able to properly reconstruct the dynamics of the active stream length as a function of antecedent precipitation. The models suggest that rainfall timing and intensity represent major controls on the stream network length, while evapotranspiration has a minor effect on the observed intraseasonal changes of drainage density. Our results also indicate the presence of multiple network expansion and retraction cycles that simultaneously operate at different time scales, in response to distinct hydrological processes. Furthermore, we found that observed spatial patterns of network dynamics and unchanneled lengths are related to the underlying heterogeneity of geological attributes. The study offers novel insights on the physical mechanisms driving stream network dynamics in low‐order alpine catchments. Key Points: We present the results of a high‐resolution survey of drainage network dynamics in the Alps Most of the observed streams are dynamical, and spatial patterns of drainage density are driven by geologic heterogeneity The temporal dynamics of the active stream length are controlled by both short‐term and long‐term antecedent rainfall